Integrating family and school, a challenge to accomplish / Integrar familia y escuela, un desafío por lograr - Moreno Acero, Iván Darío; Pinto Mantilla, Sara Jeaneth; Soto Gómez, Martha Isabel; Holguin Uribe, Natalia (RICSH Revista Iberoamericana de las Ciencias Sociales y Humanísticas, 2016)
The present study titled “Strategies of Family and School Integration” conducted at the University of La Sabana (Colombia) had two goals: academic research and Action Research (AR). The first objective was to “analyze the family integration strategies into the formation processes within the school context”. In order to achieve this objective, 38 parents were interviewed, as well as 12 teachers and 4 students from the Robert Francis Kennedy School IED in Bogota, Colombia. The primary finding indicated that there are no permanent integration strategies that are clear or attractive enough to capture the actors’ attention. Moreover, the ones that had been set up had serious structural failures due to the lack of basic organizational criteria, which limited the degree of their effectiveness. The second objective was to "design an effective strategy that integrated the family into the school in order to facilitate and promote the formation processes”. To achieve this IA goal, both their experiences and expectations regarding the relation between family and school were recovered. This process facilitated the creation, implementation and evaluation of a strategy that confirmed that the acknowledgment of the actors’ interests is fundamental, as well as the fact that all three entities (families, teachers and students) must work collaboratively since they all share the common goal of educating.